Pengaruh Komunikasi Interpersonal Skill terhadap Dunia Kerja - Aulia Monica; Sonia Ritonga; Suhairi Suhairi (STIT Sirojul Falah Bogor, 2022)
Interpersonal skill (interpersonal ability) is the ability to recognize and respond appropriately to one's feelings, attitudes and behavior, motivations and desires. This ability is very necessary because in everyday life it is almost impossible for humans not to relate to other people. In the scheme of living together arises the need to understand the needs of other human beings. Good and effective interpersonal communication skills are needed by humans so that they can carry out all their activities smoothly. Especially when someone performs activities in formal situations, for example in a work environment. More importantly, when a person's work activities are face-to-face with other people, most of the activities are interpersonal communication activities Keywords: Interpersonal Skill, Motivation,attitude and behavior.